2015
DOI: 10.1186/s12933-015-0283-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcome in patients with acute coronary syndrome and dysglycaemia

Abstract: BackgroundDiabetes and impaired glucose tolerance (IGT) are major risk factors for atherosclerosis including coronary artery disease (CAD). The present study’s aim was to investigate the importance of glucose tolerance for long-term clinical outcome in patients with acute coronary syndrome (ACS).MethodsA total 1062 consecutive patients, 781 men and 281 women, aged 32–80 years, admitted to the coronary care unit at Danderyd University Hospital, Stockholm, for ACS from 2006 to 2008 were included. At discharge, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 48 publications
0
27
0
1
Order By: Relevance
“…In fact, the undesirable physiological or psychological responses of patients during hospitalization can lead to numerous nursing activities (Hinno et al, ; Liu et al, ; Tsai et al, ). Such undesirable problems will eventually worsen the patient's condition, which will affect their long‐term outcome after hospital discharge (Kuhl et al, ). Therefore, in the present study, we applied a new method to measure the actual level of nursing activities, and we eventually found a relationship with long‐term clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the undesirable physiological or psychological responses of patients during hospitalization can lead to numerous nursing activities (Hinno et al, ; Liu et al, ; Tsai et al, ). Such undesirable problems will eventually worsen the patient's condition, which will affect their long‐term outcome after hospital discharge (Kuhl et al, ). Therefore, in the present study, we applied a new method to measure the actual level of nursing activities, and we eventually found a relationship with long‐term clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Kuhl et al have reported the percentage of NGT was 28% among 1062 ACS patients [31]. Lenzen et al confirmed 24% of NGT patients among 3940 CAD patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…Lenzen et al confirmed 24% of NGT patients among 3940 CAD patients [32]. Thus, there have been many patients with potentially unidentified and untreated DM or IGT in this population [31, 32]. The Study To Prevent Non-Insulin-Dependent Diabetes Mellitus (STOP-NIDDM) suggested that the treatment of IGT patients with an α-glucosidase inhibitor was associated with a significant reduction in the risk of cardiovascular disease [5].…”
Section: Discussionmentioning
confidence: 99%
“…Eccentric plaque refers to plaque that builds up itself on the wall of the arteries or plaque whose thickest part is more than twice of its thinnest one [9][10][11].…”
Section: Study On the Features Of Coronary Artery Atheromatous Plaquementioning
confidence: 99%